2008
DOI: 10.1093/hmg/ddn279
|View full text |Cite
|
Sign up to set email alerts
|

Rab8b GTPase, a protein transport regulator, is an interacting partner of otoferlin, defective in a human autosomal recessive deafness form

Abstract: Mutations within OTOF encoding otoferlin lead to a recessive disorder called DFNB9. Several studies have indicated otoferlin's association with ribbon synapses of cochlear sensory hair cells, as well as data showing the protein's presence in neurons, nerve fibers and hair cells, suggesting a more ubiquitous function. Otoferlin's co-localization not only with ribbon synaptic proteins, but also with additional endosomal (EEA1) or Golgi proteins (GM130) were motivation for a search for further binding partners of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 31 publications
1
57
0
1
Order By: Relevance
“…Proteins were extracted using the NucleoSpin RNA/protein kit (Macherey-Nagel) following the manufacturer's instructions. SDS-PAGE and Western blotting were performed using the "XCell II SureLock Mini-Cell and XCell II Blot Module" (Invitrogen), as previously described (Heidrych et al, 2008). The blotted proteins were incubated with either rabbit polyclonal or mouse monoclonal antibodies: BDNF (Santa Cruz Biotechnology); GAPDH (Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were extracted using the NucleoSpin RNA/protein kit (Macherey-Nagel) following the manufacturer's instructions. SDS-PAGE and Western blotting were performed using the "XCell II SureLock Mini-Cell and XCell II Blot Module" (Invitrogen), as previously described (Heidrych et al, 2008). The blotted proteins were incubated with either rabbit polyclonal or mouse monoclonal antibodies: BDNF (Santa Cruz Biotechnology); GAPDH (Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…However, subcellular localization studies have led to conflicting conclusions. An immunogold staining study reports localization to synaptic vesicles (Roux et al, 2006), whereas immunofluorescence indicated that otoferlin is localized predominantly in the Golgi and possibly in early endosomes (Schug et al, 2006;Heidrych et al, 2008). Thus, otoferlin may have alternative or additional functions, such as vesicle recycling or membrane trafficking in the Golgi.…”
Section: Otoferlin Is a Calcium Sensormentioning
confidence: 99%
“…Thus, otoferlin may have alternative or additional functions, such as vesicle recycling or membrane trafficking in the Golgi. Recently, it was reported that point mutations within otoferlin resulted in plasma membrane infolding (Heidrych et al, 2008). This suggests a role for otoferlin in the endocytosis and vesicle recycling and could explain why otoferlin IHC knockouts exhibit defects in exocytosis.…”
Section: Otoferlin Is a Calcium Sensormentioning
confidence: 99%
“…Its subcellular distribution beyond regions of synaptic vesicle fusion and its association with Golgi markers suggested a more ubiquitous role. Protein-protein association studies demonstrated that otoferlin can not only interact with syntaxin 1 and Snap25, both ribbon synaptic components (27) but with Rab8 and Myo6, two proteins involved in the transGolgi network and in cargo sorting (31,32). Screening for otoferlin's partners using the yeast-2-hybrid system suggested further candidates (33) ( Table I).…”
Section: Otoferlin's Interactomementioning
confidence: 99%